Acupuncture and regulation of gastrointestinal function - Li, Hui (World journal of gastroenterology : WJG, 2015)
In China, acupuncture has been considered aneffective method for treating gastrointestinal （GI）dysfunction diseases for thousands of years. In fact,acupuncture has gained progressive acceptance fromboth practitioners and patients worldwide. However,the therapeutic effects and underlying mechanisms intreating GI dysfunction have not yet been establisheddue to a lack of systematic and comprehensive reviewarticles. Therefore, the aim of this review is to discussthe efficacy of acupuncture as a treatment for GIdysfunction and the associated underlying mechanisms.A search of PubMed was conducted for articles thatwere published over the past 10 years using the terms＂acupuncture＂, ＂gastrointestine＂, and other relevantkeywords. In the following review, we describe theeffect and underlying mechanisms of acupuncture onGI function from the perspectives of GI motility, visceralsensitivity, the GI barrier, and the brain-gut axis. Thedual regulatory effects of acupuncture may manifest bypromoting gastric peristalsis in subjects with low initialgastric motility, and suppressing peristalsis in subjectswith active initial motility. In addition, the regulationof acupuncture on gastric motility may be intensitydependent.Our findings suggest that further studies areneeded to investigate the effects and more systematicmechanisms in treating GI dysfunction, and to promotethe application of acupuncture for the treatment of GIdiseases.